แนวทางเพิ่มประสิทธิภาพการบริหารโครงการอาหารกลางวันของโรงเรียนบ้านบางแก้ว - พวงมาลา จินดาหรา; เก้าเอี้ยน สุรศักดิ์ (An Online Journal of Education, 2018)
The research aimed to analyze efficiency and study the management of lunch project in Banbangkeaw School. In addition, to propose the approaches for increase the efficiency of lunch project management in Banbangkeaw School. 14 school staff consisted of the school principal and teachers and 150 students were research respondents. The data were collected by authentic measurement and using the questionnaire of approaches for increase the efficiency of school lunch project management in Banbangkeaw School. Quantitative data was analyzed using frequency, distribution, percentage mean and standard deviation, while qualitative data was analyzed using content analysis. The results indicated 1) the efficiency of lunch project in Banbangkeaw School in the cost of discarded food is 20 percent. Have quality of food in 5 nutrients, Have time to eat discrepancy average 12 minutes. Satisfaction of clients who have lunch have medium rate of satisfaction ( = 3.12). And the lunch service providers was medium rate satisfaction ( = 2.74). 2) The same as condition of lunch project management it in medium rate satisfaction ( = 2.74). When considering in each aspects of mean rank respectively, was: Implementation of the plan into action ( = 2.96). Evaluation ( = 4.79) and Planning ( = 2.49) 3) The approaches for increase the efficiency of lunch project management in Banbangkeaw School should emphasize 4M Man, Money, Material and Management by using PDCA for management in each part to increase the efficiency of lunch project management.